Design methodology using empirical and virtual analysis with application to compliant systems - Wood, John Joseph, author; Troxell, Wade, advisor; Sakurai, Hiroshi, committee member; Jensen, Daniel, committee member; Bjostad, Louis, committee member (Colorado State University. Libraries, 2002)
Successful engineering design results from die application of suitable product design methods to an identified customer need. The generation and evaluation of conceptual designs satisfying engineering and customer requirements is a primary purpose of existing methods. Numerical and experimental techniques often can determine the feasibility of meeting the specified performance requirements.

The concept generation design phase is expanded through a formalized process geared toward die design evolution of products characterized specifically by reduced part count through the incorporation of compliant materials and structures. Compliance offers a new dimension to evolutionary product design by introducing flexible components for direct component combination or replacement. Effort flow analysis is a technique that provides a framework for identifying component combination opportunities. This graphical method maps the flow of effort across component interfaces and systematically provides insights based upon the type of relative motion required between them.

A formalized method for identifying and classifying these component groups is developed. An empirical study of existing products is conducted with the outcome being a deduced set of product evolution specific directive guidelines. The derived guidelines support the directed product evolution effort flow analysis methodology.

Evaluation of conceptual designs is critical in the determination of functional performance. Similarity methods offer performance predictions of products based upon functional testing of scale models to correlate measured model behavior with predicted product behavior. Traditional methods can be improved in both accuracy and domain of applicability by the infusion of empirical data, derived from simplified tests, into the equations that characterize the system parameters of interest. Similarity methods have been developed that overcome the constraints associated with the traditional methods and provide increased analysis capability and improved insight into the phenomenon governing the problem.

The product evolutionary design methodology incorporates an analytical feasibility determination to provide a conceptual design and evaluation approach for design focusing on component combination and incorporation of compliant solutions. The method has demonstrated successful evolutionary design of compliant systems and accurate similarity-based predictions of product performance. Future endeavors include expansion of effort flow analysis and advanced similarity methods to include the design of systems outside the mechanical domain.
Keywords: mechanical engineering; industrial engineering